The Influence of Augmented Reality on Purchase Intention in the Housing Industry - F. A. Ibrahim; W. Boying; N. S. Abdul Rahim; M. W. Mohd Shafiei; N. Z. Zainol (Human Behavior and Emerging Technologies)
Rapid emergence of technology communication has demanded the business organization to adapt with the most optimal marketing approach to ensure long-term survival in the modern business environment. Research on technologies adaptation in relation to marketing were conducted in various sectors in order to study the marketing communication channels in persuading targeted customers to purchase the selling products or utilize the services offered in the market. In contrast, the advancement of technology was not thoroughly harnessed by the property sector, which lagged in adopting the innovative marketing approach to promote their selling house. Accordingly, this research is aimed at investigating the effect of marketing communication channels via the adoption of AR to encourage the intention to purchase among the targeted house buyers. A total of 130 booklets of survey forms were distributed using the self-administered method along with the prompt material of housing design in AR applications. In return, 100 booklets of survey forms were received. As a result, the findings indicated that AR application as a marketing communication channel has an impact on the intention to purchase among potential house buyers. It is expected that AR technologies would create a new norm with extraordinary modification and advancement to promote housing projects and provide guidance to the developer. This initiative is able to improve their marketing communication, thus attracting house buyers based on their interests.